EDUKASI HUKUM & DEMOKRASI PADA SANTRI PONDOK PESANTREN AL-AMIN PAJAJARAN - Zulkarnaini, Umar; Mukharrom, Miftakhul; Kamal, Musthafa; Qalbi, Raihanul; Suparta, Endang; Erlina, Erlina; Amanda, Amanda; Jannah, Putri Naurah (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to analyze and develop a legal and democracy education program among students at the Al-Amin Pajajaran Islamic Boarding School. This program aims to increase students' understanding of legal principles and democratic values ​​in social and state life. The research uses a descriptive-qualitative method with in-depth interviews, observation and documentation studies as data collection techniques. The research results show that students have a basic understanding of law and democracy, but this needs to be improved through an interactive and contextual based approach.